ภาวะตื่นรู้เชิงพุทธบูรณาการ - สัสสินทร สาริศา (Academic Psychiatry and Psychology Journal, 2016)
วัตถุประสงค์ เพื่อศึกษาภาวะตื่นรู้ตามหลักพุทธบูรณาการ วัสดุและวิธีการ การวิจัยนี้เป็นการวิจัยเชิงเอกสาร (documentary research) โดยรวบรวมข้อมูลชั้นปฐมภูมิ (primary sources) จากพระไตรปิฎกและอรรถกถา และรวบรวมข้อมูลชั้นทุติยภูมิ (secondary sources) จากหนังสือ ตำรา เอกสารทางวิชาการ และงานวิจัยที่เกี่ยวข้องทั้งในภาษาไทยและภาษาต่างประเทศ นำเสนอโดยใช้การพรรณนา (descriptive) ผลการศึกษา พระพุทธศาสนามีทัศนะว่า มนุษย์หรือสัตว์ในโลกนี้มีส่วนประกอบที่สำคัญของร่างกายอยู่ ๒ ส่วน คือ กายและจิต แต่ให้ความสำคัญกับจิตเพราะเป็นตัวควบคุมพฤติกรรมที่กายแสดงออกมา และมีหลักการว่าจิตสามารถฝึกฝนได้ตามแนวทางสติปัฏฐานจนบรรลุเป้าหมายสูงสุดคือภาวะตื่นรู้ ซึ่งเป็นการพัฒนาจิตที่สมบูรณ์ด้วยสติและสัมปชัญญะ ก่อให้เกิดประโยชน์ในระดับปัจเจกบุคคลในด้านการพัฒนาพฤติกรรม จิตใจและสติปัญญา บุคคลที่เข้าถึงภาวะตื่นรู้ย่อมเข้าใจชีวิตและมีความสุขท่ามกลางปัญหาต่างๆ ได้ สำหรับประโยชน์ระดับสังคมคือการสร้างวัฒนธรรมแห่งการตื่นรู้เพื่อเป็นประโยชน์ต่อการดำรงชีวิตในกระแสบริโภคนิยม สรุป ภาวะตื่นรู้เชิงพุทธบูรณาการเป็นการประยุกต์หลักการเจริญอานาปานสติภาวนาตามหลักของศีล สมาธิและปัญญาให้เข้ากับวิถีการดำเนินชีวิตประจำวัน The Awakening on Buddhist Integration Objective To study the awakening on Buddhist integration Materials and Methods This descriptive research was conducted through the documentary research method. All primary data were collected from the Tipitaka and Commentaries and the secondary data were collected from texts, academic papers and related research both in Thai and foreign languages. Results According to the concept of Buddhism, human beings and all living creatures consist of two parts i.e. physical and mental. However, Buddhism emphasizes mentality as controlling physical behaviors. The human mind can also be trained in line with the Four Foundation of Mindfulness to achieve the Ultimate Goal or the awakening state of mind. This is the model of mental development with Sati-sampajayya: mindfulness and awareness. A person who realizes the awakening state understands life and can be happy when facing problems. The social benefit is to create the awakening culture for the sake of living in the consumerist society. Summary The Buddhist Integrated on the Awakening Model is an application of developing the Anapanasati: mindfulness on breathing based on the right mindfulness and concentration in daily life.